The Impact of Socioeconomic Position on Severe Maternal Morbidity Outcomes Among Women in Australia: A National Case-control Study. Issue 3 (September 2016) - Lindquist, A.; Noor, N.; Sullivan, E.; Knight, M.
Abstract : ( BJOG. 2015;122(12):1601–1609) Research conducted in Australia in 2000 determined that although there had been improvements in the health of the population over previous years, increased inequalities for socioeconomically related mortality had occurred for some conditions. Studies in other developed countries, such as the United Kingdom, have suggested that socioeconomic position may be a risk factor for poorer pregnancy outcomes. Identifying high-risk parturients is critical for the prevention of adverse pregnancy outcomes because it allows targeted interventions and intensive clinical management of specific groups of women. The Australasian Maternal Outcomes Surveillance System is based on the methodology of the UK Obstetric Surveillance System and enables research and surveillance for a range of pregnancy complications across Australia and New Zealand. This study aimed to explore the independent impact of socioeconomic position on selected severe maternal morbidities among women in Australia.